An Enhanced Detection Scheme and Distributed Resilient Asynchronous Event-Triggered Control of AC Microgrids Subject to Replay Attacks - Shahabadi, Masoud Zare; Atrianfar, Hajar; Abyaneh, Hossein A. (IEEE transactions on cybernetics, 2025)
The transmission of information between distributed energy resource units (DERUs) within Microgrids (MGs) relies on sensing and communication systems that are vulnerable to cybersecurity threats. This article addresses the challenge of achieving resilient synchronization in networked AC MGs under cyber-attack conditions, specifically in scenarios where adversaries aim to desynchronize converters by intercepting, recording, and replaying communication signals. To mitigate these threats, we propose a distributed resilient event-triggered mechanism (DRETM) for secondary control of AC MGs during replay attacks. Unlike existing cybersecurity strategies, the proposed asynchronous event-based scheme enhances communication efficiency and reduces network resource consumption by employing a dual trigger function tailored for the communication links between the leader and informed DERUs, as well as among neighboring DERUs. Furthermore, to improve the detection of replay attacks, an enhanced distributed watermark-based detection scheme (EDWDS) is introduced. This mechanism minimizes the adverse effects of watermark signals on the system and streamlines the detection process by eliminating the need for complex parameter calculations or neighboring state estimations, in contrast to current detection methods. Finally, simulation results conducted in MATLAB/Simulink validate the effectiveness and accuracy of the proposed mechanisms.